Denitration of Nitroesters with Tributyltin Hydride in the Presence of Azobisisobutyronitrile (AIBN) (Journal of Sciences, Islamic Republic of Iran)
Among the different reducing agents tributyltin hydride was found to be a powerful reducing agent for the denitration of a series of tertiary and secondary nitroesters. The organotin residues removed from the crude product using saturated potassium fluoride solution. The yield of the reactions was 62-98%.